THE ROLE OF INFORMATION TECHNOLOGIES IN INCLUSIVE EDUCATION - Ozoda Kuranboyeva (Web of Journals Publishing, 2024)
Inclusive education serves as an important tool in ensuring the integration of children with disabilities into society. With the help of information technologies, it is possible to adapt the educational process, teach on the basis of an individual approach, and effectively use educational resources. This article analyzes the methods of using information technologies in inclusive education and their effectiveness.
Keywords: Inclusive education, information technologies, special needs, adapted teaching, digital resources, interactive platforms.